Discrete Subaortic Stenosis: Perspective Roadmap to a Complex Disease - Massé, Danielle D.; Shar, Jason A.; Brown, Kathleen N.; Keswani, Sundeep G.; Grande-Allen, K. Jane; Sucosky, Philippe (Frontiers in Cardiovascular Medicine, 2018)
Discrete subaortic stenosis (DSS) is a congenital heart disease that results in the formation of a fibro-membranous tissue, causing an increased pressure gradient in the left ventricular outflow tract (LVOT). While surgical resection of the membrane has shown some success in eliminating the obstruction, it poses significant risks associated with anesthesia, sternotomy, and heart bypass, and it remains associated with a high rate of recurrence. Although a genetic etiology had been initially proposed, the association between DSS and left ventricle (LV) geometrical abnormalities has provided more support to a hemodynamic etiology by which congenital or post-surgical LVOT geometric derangements could generate abnormal shear forces on the septal wall, triggering in turn a fibrotic response. Validating this hypothetical etiology and understanding the mechanobiological processes by which altered shear forces induce fibrosis in the LVOT are major knowledge gaps. This perspective paper describes the current state of knowledge of DSS, articulates the research needs to yield mechanistic insights into a significant pathologic process that is poorly understood, and proposes several strategies aimed at elucidating the potential mechanobiological synergies responsible for DSS pathogenesis. The proposed roadmap has the potential to improve DSS management by identifying early targets for prevention of the fibrotic lesion, and may also prove beneficial in other fibrotic cardiovascular diseases associated with altered flow.